Meaningful practices: The contemporary relevance of traditional making for sustainable material futures. Issue 2 (1st September 2019) - Walker, Stuart; Evans, Martyn; Mullagh, Louise
This article explores the relationship between design for sustainability and traditional making practices. It presents results from key informant interviews and observational research into traditional hand making of functional goods in Santa Fe in the United States, Jingdezhen, China, various locations in New South Wales, Australia and Cumbria, United Kingdom. We find that such goods fall into three main categories, primarily utilitarian, symbolic and aesthetic. These practices are discussed in terms of their contemporary relevance, potential futures and relationship to current understandings of sustainability. More specifically, they are considered against the four elements of the Quadruple Bottom Line of Design for Sustainability (Walker 2014 ), a rigorous interpretation extended from the philosophy of Hick (1989), which comprises: practical meaning including environmental impacts; social meaning; personal meaning; and economic means. The originality of this research lies in the development of new arguments and insights with regard to the complex issues of design for sustainability and traditional making practices. Significantly, we find that many of these practices are intellectually consistent with broad, contemporary understandings of design for sustainability. However, we also find that it is often not easy to reconcile these practices with modern consumer culture. Our research shows that pursuing these practices part-time for their own sake, rather than for primarily commercial reasons can often facilitate the pursuit of excellence and the continuation of cultural traditions.